Genetic engineering in developing drought tolerance maize and its new prospects - Thu Huệ, Huỳnh Thị; Linh, Nguyễn Thùy; Hà, Nguyễn Hải (Vietnam Journal of Biotechnology, 2018)
Maize is one of the most important cereals in human civilization. However, the productivity of crops has been being adversely affected by increasing droughts as a consequence of the global climate change. Recently, the yield and production of a number of maize growing regions witnessed a significant decrease due to continuously droughts. To minimize the impacts of the water-shortage condition, many measures have been taken. Among them, genetic engineering helps enhance plant survival by transferring drought-tolerance related genes into maize. Hundreds of drought-responsive genes from maize or other species have been isolated and characterized. Those genes encode transcription factors and proteins involving in signal transduction pathways as well as cell protection mechanisms. However, in order to highly and precisely express interested genes in transgenic maize, it is necessary to modify genes by using proper codon usage frequency, adding signals of post-transcriptional, translational and post-translational regulations. Additionally, other components of transformation process such as vector systems, promoters, gene delivery procedures, etc. are required to be optimized. Results from drought-tolerant trait related studies which has been being heavily invested in are worth the effort. Recently, new genetic engineering approaches known as genome editing are being accomplished and applied to a wide range of species. The advanced techniques including ZFNs, TALENs, and CRISPR/Cas9 hold enormous potential for drought-tolerant crop development. It is believed that in the near future, genome-edited based cultivars are more elite than traditional ones.